Mappasoro' Tradition in Mandar; an 'Urf Analysis - Amir, Sapri; Lewa, Irfan (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the views of Islam ('urf perspective) against a tradition that is still commonly practiced by the Mandar community today is the mappasoro tradition, especially in Laliko Village, Campalagian District, Polewali Mandar Regency. This research does not aim to be seen as an act that has implications for reward or sin when it is done or not done, but want to see the values contained in this tradition so that they are still used today. This type of research is field research where the researcher is required to go directly to the field by using a qualitative descriptive research method, namely research that provides an overview of the mappasoro tradition in the 'urf perspective' carried out by the community in the village. This research uses a social approach and a syar'i approacpp. The results of this study indicate that the mappasoro tradition is a tradition that is considered a form of alms that is carried out solely to remember Allah SWT. even in this tradition it contains religious values, moral values, and cultural values